FUNGSI GAYA BAHASA PERULANGAN DALAM ANTOLOGI PUISI GURU MUSAFIR ILMU KARYA 97 GURU 3 NEGARA (TINJAUAN STILISTIKA - Taufik Rohman; Sukarismanti; Rusmin Nurjadin (MANTRA: Jurnal Sastra Indonesia (Sastra, Bahasa, Budaya), 2023)
The purpose of this research is to describe the language style of repetition of alliteration and assonance found in the Anthology of Guru Musafir Ilmu's Poetry: 97 Guru 3 Negara. This study utilizes stylistic theory as a tool to help researchers dissect the object of study. The method used in this research is descriptive qualitative method. The source of the data is the Poetry Anthology of Pilgrims of Science by 97 Teachers from 3 Countries. The data analyzed in this study are the language style of repetition of alliteration and assonance in the Anthology of Guru Musafir Ilmu's Poems by 97 Teachers of 3 Countries. The results of this study indicate that language style is used by poets to add aesthetic value to the poetry they produce. The use of repetition language style in the form of alliteration serves to emphasize something that is many and continuous and emphasizes an identity. The use of repetition language style in the form of assonance serves to emphasize the personality and identity of a person or character in poetry, emphasizes the personality of a person or character in poetry, and confirms the personality of a person or character in the poem.